The role of diagnostic ultrasound as a new diagnostic aid in oral and maxillofacial surgery - Siva Subramaniyam Venkataraman; Ramraj Jayabalan Aravind; Thangavelu Kavin (Wolters Kluwer Medknow Publications, 2012)
Only very few studies have been done in the past to evaluate the usefulness and limitations of ultrasonography in oral and maxillofacial surgery. This study, though in an embryonic stage, has been done to bring this technique to limelight and to put forth the importance of its use and limitations in the branch of oral surgery. The purpose of this study was to investigate and study the characteristic pattern of the oral tissues on gray scale ultrasonography and to assess the practical applicability of this new diagnostic technique in diagnosing various tissue pathologies in the field of oral and maxillofacial surgery.